Brindar asistencia técnica a la secretaría de infraestructura municipal de Duitama en la revisión de proyectos civiles. (2023)
In the municipal government of the city of Duitama, there are challenges with backlogged projects due to a change in legal representation resulting from atypical elections. This has led to delays in proposals for pre-feasibility studies, adversely affecting the community. Two years ago, when the current mayor assumed office in Duitama, the urban road network was in poor condition due to a lack of investment and adverse weather conditions. Duitama's urban road network is now in an advanced state of deterioration, characterized by cracked pavement and potholes, impeding traffic flow, and posing a risk to the community. Addressing this issue requires a comprehensive intervention that identifies critical segments and implements rehabilitation measures alongside long-term maintenance strategies. The intern plays a pivotal role by conducting field inspections to oversee construction works, ensuring compliance with technical specifications. Additionally, they contribute to the creation and monitoring of project schedules. Furthermore, they actively participate in the supervision of patching, pothole repair, and maintenance activities, acquiring technical skills and ensuring adherence to standards.